2007
DOI: 10.1111/j.1746-1561.2007.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Promising Outcomes in Teen Mothers Enrolled in a School‐Based Parent Support Program and Child Care Center

Abstract: For at-risk teen mothers, this parent support program and school-based child care setting appears to offer promising opportunities to help young mothers with parenting, avoid rapid subsequent pregnancies, and stay engaged with school, while their children are cared for in a close and safe environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 29 publications
1
50
0
Order By: Relevance
“…162 Feelings of support and connectedness can increase self-esteem, self-competence and empowerment, which, as stated previously, can in turn lead to greater feelings of control over self, choices and outcomes. Being connected to the intervention, group or others can also have the added benefit of helping to keep mothers on track with the changes they propose to make.…”
Section: Theory Formation: Why Interventions Might Work and For Whom mentioning
confidence: 90%
See 3 more Smart Citations
“…162 Feelings of support and connectedness can increase self-esteem, self-competence and empowerment, which, as stated previously, can in turn lead to greater feelings of control over self, choices and outcomes. Being connected to the intervention, group or others can also have the added benefit of helping to keep mothers on track with the changes they propose to make.…”
Section: Theory Formation: Why Interventions Might Work and For Whom mentioning
confidence: 90%
“…In the UK, this is currently not an option; however, evidence from the USA demonstrates positive results when interventions are delivered in schools. 97,107,109,162 This approach embeds the intervention in the mother's lives, keeping the focus on education, but also allowing them to have contact with their children during the day. Providing childcare in a school as part of a wider intervention acknowledges the dual role of the adolescent mother; she is still an adolescent who needs to complete her education, but she is a mother who feels responsible for her child and needs to know that they are safe and well cared for while she is attending classes.…”
Section: Situating the Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, it would be expected that all adolescent females in this study would recognize the importance of delaying subsequent pregnancies, which was supported in the data. Similarly, Sadler et al found that adolescent mothers were more likely to delay subsequent pregnancies and stay engaged in school when they were enrolled in a school-based parent support program [17]. Likewise, Sangalang, Barth, and Painter noted adolescent mothers postponed subsequent births after receipt of case management and direct services from social workers [18].…”
Section: Discussionmentioning
confidence: 99%